STUDI KOMPARATIF STIGMA TERHADAP ODHA PADA MAHASISWA TINGKAT I DAN TINGKAT III AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Wiwin Winarni; Sesilia Natasya Aulia (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background : Giving stigma toward people who live with HIV/AIDS is not only can befound on common people who live in society but also among health workers. It isunbelievable if health workers whose education background is health will do the samething toward people living with HIV/AIDS. Thus, it is necessary to have some strategies toprepare nursing students in order to reduce the discrimination which happen in healthservices facilities by health workers. Hence, the prevention efforts of HIV/AIDS cases inIndonesia can optimally be implemented.The purpose of this study : was to analyze the diversity of stigma level toward peopleliving with HIV/AIDS between the first year students and the third year students in PantiKosala Nursing Academy.This research used analytic with comparative design. The total population involved in thisresearch were 150 students of Panti Kosala Nursing Academy which was then dividedinto two groups. Group number one was consisted of 75 students from grade one andgroup number two was consisted of 75 students from grade three. Random sampling wasused as a sampling technic. Data was collected by using questionnaire. The data wasthen analyzed using Mann-Whitney aided by SPSS serial 16.There were three main results of this study : 1) The majority of first year students havehigh level of stigma toward people living with HIV/AIDS accounted for 57,33%. 2)Themajority of third year students have high level of stigma toward people living wthHIV/AIDS accounted for 53,33%. 3)The analysis of Mann-Whitney shows significancynumber p>0,721. It can be concluded that the stigma toward people living with HIV/AIDSof first year students as same as with the one of third year students.Keywords: stigma, people living with HIV/AIDS, nursing students